FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2012-2016 - Wisyelia Tjiangdiono; Werner Ria Murhadi; Endang Ernawati (Perpustakaan Universitas Surabaya, 2018)
This research aims to analyze the determinants of capital structure for non-financial companies registered in Indonesia Stock Exchange in 2012-2016. Variables which use are size, tangibility, growth, profitability, andnon-debt tax shield. The related theories being used in this research are pecking order theory,trade off theoryandagency theoryThis research uses the quantitative approach and multiple linear reggresion to analyze the data. The target populations of this study are all non-financial companies registered in Indonesia Stock Exchange in 2012-2016 which are equal to 1420 year observations.The research finds that size, tangibilityandprofitabilityaffect capital structure negatively. On the other hand, growthandnon-debt tax shield affect capital structure positively.